Konsentrasi Sludge Minyak Bumi dalam Proses Bioremediasi Memanfaatkan Bakteri Indigen dan Lamtoro Gung - Arief Alghifari; Sri Pertiwi Estuningsih; Nina Tanzerina (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
This research aimed to determine synergies between bacteria indigen with lamtoroin bioremediation processes at various concentrations of sludge through the measurement ofvariables, and the number of bacteria, impairment of Total Petroleum Hydrocarbons (TPH), andweight of lamtoro gung. Experimental design used was Complete Randomized Design (CRD) with5 treatments and 5 replications, increase the concentration sludge treatment is control (0%), 2.5%,5%, 7.5%, and 10% of sludge. The study found that given sludge concentration increases causingthe higher number of bacterial populations. Sludge concentration decreased significantly affectTPH values and highest TPH values decrease at 7,5% concentration of sludge. Sludgeconcentration significanly affect the wet weight and given treatment sludge, Lamtoro wet wieghtdecreased at the end ofthe study